PENGARUH KUAT ARUS PENGELASAN GMAW TERHADAP KEDALAMAN PENETRASI DAN KEKERASAN BAJA ST-37 PADA DAERAH HEAT AFFECTED ZONE - Agus Fikri; Kurniawan Setiyadi; Mohammad Mujirudin (Universitas Negeri Jakarta, 2022)
The selection of proper current is closely related to the depth of penetration of welds on metal and will affect the mechanical properties of the resulting welded joints. The purpose of this study was to determine the effect of current on penetration depth, welding width, and hardness in the Heat Affected Zone (HAZ). The research method used is experimental with currents of 180 A, 200 A, and 220 A. Welding is done on ST-37 steel using the GMAW welding technique. Penetration depth for components 1 and 2 with a current of 180 A are 0.77 mm and 0.78 mm, respectively, at a current of 200 A are 1.29 mm and 1.06 mm, and in 220 A are 1 .52 mm and 1.44 mm. The resulting welding width for 180 A is 5.86 mm, at 200 A is 6.70 mm, and at 220 A is 7.35 mm. Meanwhile, the hardness of the HAZ area shows that at a current of 180 A the hardness is 122 HV, while for a current of 200 A and 220 A the hardness is 120.5 HV. The quality standard of welded joints at each current indicates that the resulting penetration depth is more than 20%, so it can be said that the welding process has met the minimum standards.